Mainstreaming Climate Governance through Massive Open Online Courses (MOOCs): A Strategy for Scaling Climate Literacy in Sub-Saharan Africa. - Bukola ODEDIRAN (RADINKA JAYA UTAMA PUBLISHER, PADANG< INDONESIA, 2026)
Sub-Saharan Africa (SSA) bears a disproportionate burden of climate change impacts relative to its contribution to global emissions, yet persistent gaps in governance capacity and environmental education undermine effective policy response and community-level adaptation. Massive Open Online Courses (MOOCs) have emerged as a digital education modality capable of transcending geographical, institutional, and financial barriers, but their application to climate governance education in SSA remains largely unexplored. This paper examines MOOCs as a strategic instrument for scaling climate literacy and mainstreaming climate governance principles across SSA. A systematic narrative review and conceptual synthesis of literature published between 2015 and 2025 was conducted across Scopus, Web of Science, and Google Scholar. Forty-seven studies were analysed through thematic synthesis, integrated with MOOC completion data, climate governance indices, and policy documents including the Paris Agreement, AU Agenda 2063, and Nationally Determined Contributions from fifteen SSA countries. Findings confirm a critical climate literacy deficit correlated with governance effectiveness indices (r = 0.74, p < 0.01 across 32 countries). Fewer than 3% of available climate MOOCs target SSA contexts, and African learner completion rates average 8.2% versus 14.6% globally. The proposed Contextualised Climate MOOC (CC-MOOC) framework addresses these barriers through six integrated design principles, projecting annual reach of 2.4–4.8 million learners if adopted within existing national curricula. MOOCs represent an underutilised but high-potential vehicle for democratising climate governance knowledge in SSA, demanding contextually grounded, digitally equitable implementation ecosystems.